Separation of (3.14C) 3-Hydroxy.3-methylglutaric acid from (3_14C) 3-Hydroxy-3-methylglutaryl CoA using Sephadex G-15 column chromatography - Sipat, Abdullah; Sabine, John R. (1981)
A new method has been developed for the separation of (3- 14C) 3-Hydroxy-3-methylglutaric acid from a (3-14C) 3-Hydroxy-3-methylglutaryl CoA preparation using Sephadex G-15 column chromatography. This method is simple, rapid and is useful in studies where the preparation of (3_ 14C) 3-Hyd1'oxy-3-methylglutaryl CoA is required to bef1'eef1'Om (3_ 14C) 3-Hydroxy-3-methylgluta1'ic acid contamination.